PagWOX11/12a positively regulates the PagSAUR36 gene that enhances adventitious root development in poplar. (24th August 2022) - Liu, Rui; Wen, Shuang-Shuang; Sun, Ting-Ting; Wang, Rui; Zuo, Wen-Teng; Yang, Tao; Wang, Chao; Hu, Jian-Jun; Lu, Meng-Zhu; Wang, Liu-Qiang
Abstract : We identified that the WOX11/12a– SMALL AUXIN UP RNA36 module mediates adventitious root development through the auxin pathway in poplar, and enhances rooting in response to salt stress. Abstract: Adventitious root (AR) development is an extremely complex biological process that is affected by many intrinsic factors and extrinsic stimuli. Some WUSCHEL-related homeobox (WOX) transcription factors have been reported to play important roles in AR development, but their functional relationships with auxin signaling are poorly understood, especially the developmental plasticity of roots in response to adversity stress. Here, we identified that the WOX11/12a– SMALL AUXIN UP RNA36 ( SAUR36 ) module mediates AR development through the auxin pathway in poplar, as well as under salt stress. PagWOX11/12a displayed inducible expression during AR development, and overexpression of PagWOX11/12a significantly promoted AR development and increased salt tolerance in poplar, whereas dominant repression of PagWOX11/12a produced the opposite phenotype. PagWOX11/12a proteins directly bind to the SAUR36 promoter to regulate SAUR36 transcription, and this binding was enhanced during salt stress. Genetic modification of PagWOX11/12a–PagSAUR36 expression revealed that the PagWOX11/12a –PagSAUR36 module is crucial for controlling AR development via the auxin pathway. Overall, our results indicate that a novel WOX11 –SAUR –auxin signaling regulatory module is required for AR development in poplar. These findings provide key insights and a better understanding of the involvement of WOX11 in root developmental plasticity in saline environments.